The prevalence of CYP2D6*10 (100C>T, rs1065852) gene polymorphism in Russian patients with epilepsy (North-Western and Siberian Districts) - N. A. Sivakova; N. A. Shnayder; D. V. Dmitrenko; L. V. Lipatova; M. Y. Tolmachev; R. F. Nasyrova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The gene CYP2D6 is of great interest also due to its highly polymorphic nature and involvement in a high number of medication metabolisms. The presence of polymorphisms in the CYP2D6 gene may modulate enzyme level and activity, thereby affecting individual responses to pharmacological treatment.  The purpose of this study was to investigate of CYP2D6*10 polymorphism prevalence in patients with epilepsy in the North-West and the Siberian region of the Russia. The results of the study showed differences in the prevalence of alleles responsible for “intermediate” metabolites in the North-West and Siberian regions of Russia were identified, it’s may be associated with genetic drift and accumulation of alleles typical for European and Asian populations.